2016
DOI: 10.5505/tjtes.2016.93288
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Revised Trauma Score, Injury Severity Score and Trauma and Injury Severity Score for Mortality Prediction in Elderly Traumatic Patients

Abstract: BACKGROUND: Trauma is the fifth leading cause of death in patients 65 years and older. This study is a comparison of results of Revised Trauma Score (RTS), Injury Severity Score (ISS), and Trauma and Injury Severity Score (TRISS) in prediction of mortality in cases of geriatric trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In a study by Yousefzadeh-Chabok et al ., mean plus standard deviation of ISS for non-survivors was 15.95±10.46 and 7.31±6.22 for survivors; mean plus standard deviation of RTS for former was 5.65±1.82, and 7.79±0.27 for latter group. Mean plus standard deviation of TRISS for non-survivors was 1.04±1.49 and was 3.49±0.6 for survivors 23 .…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…In a study by Yousefzadeh-Chabok et al ., mean plus standard deviation of ISS for non-survivors was 15.95±10.46 and 7.31±6.22 for survivors; mean plus standard deviation of RTS for former was 5.65±1.82, and 7.79±0.27 for latter group. Mean plus standard deviation of TRISS for non-survivors was 1.04±1.49 and was 3.49±0.6 for survivors 23 .…”
Section: Methodsmentioning
confidence: 92%
“…In Aydin et al study, area under ROC curve using ISS, NISS and TRISS for predicting death was 0.907, 0.914 and 0.934, respectively 22 . In Yousefzadeh-Chabok et al study, area under ROC curve using ISS, RTS and TRISS for predicting death was 0.76, 0.87 and 0.94, respectively 23 .…”
Section: Methodsmentioning
confidence: 92%
“…Most studies showed that the NISS and TRISS were better than the ISS for the prediction of outcome in trauma patients [ 31 ]. Yousefzadeh-Chabok et al reported the AUCs of the ISS and TRISS in predicting mortality among geriatric trauma patients were 0.76 and 0.94 [ 32 ]. Homanna Javali et al also compared the ISS, NISS, and TRISS for predicting mortality in cases of geriatric trauma, and the corresponding AUCs were 0.963, 0.970, and 0.972, respectively [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of results of RTS or ISS, TRISS was a stronger predictor of mortality in elderly trauma patients as result of the combination of both anatomical and physiological parameters [ 16 ]. A hybrid model incorporating the anatomical and physiological aspects of the trauma patients is expected to have heightened discriminatory abilities for predicting mortality outcomes.…”
Section: Discussionmentioning
confidence: 99%